PELABELAN GRACEFUL SISI BERARAH PADA GRAF GABUNGAN GRAF SIKEL DAN GRAF STAR - Octafiani, Putri; Utomo, Robertus Heri Soelistyo (MATEMATIKA, 2013)
Let G is simple and finite graph. Graph G is called a directed edge-gracefull graph if there exists an orientation of G and bijective map f : A(G) → 1,2, ..., q such as a map g on V defined by g(v) = [f +(v) – f –(v)] (mod p) is bijective map, which is f +(v) is the sum of the labels of arcs with v as a head and f –(v) is the sum of the labels of all arc with v as a tail. Graph with directed edge-gracefull labeling is called directed edge-gracefull graph. In this paper we will discussed about directed edge-gracefull labeling of cycle and star related graph